2015
DOI: 10.1051/0004-6361/201525954
|View full text |Cite
|
Sign up to set email alerts
|

Cepheid distances from the SpectroPhoto-Interferometry of Pulsating Stars (SPIPS)

Abstract: Context. The parallax of pulsation, and its implementations such as the Baade-Wesselink method and the infrared surface brightness technique, is an elegant method to determine distances of pulsating stars in a quasi-geometrical way. However, these classical implementations in general only use a subset of the available observational data. Aims. Freedman & Madore (2010, ApJ, 719, 335) suggested a more physical approach in the implementation of the parallax of pulsation in order to treat all available data. We p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 61 publications
6
84
0
Order By: Relevance
“…It is clear from this diagram that the linear and quadratic parametric models are poor representations of the actual intensity profile of the Sun. This was also the conclusion reached, for example, by Heyrovský (2007), Mérand et al (2015) and Espinoza & Jordán (2016). The square root model and the four-parameter law introduced by Claret (2000) appear to be better approximations.…”
mentioning
confidence: 75%
“…It is clear from this diagram that the linear and quadratic parametric models are poor representations of the actual intensity profile of the Sun. This was also the conclusion reached, for example, by Heyrovský (2007), Mérand et al (2015) and Espinoza & Jordán (2016). The square root model and the four-parameter law introduced by Claret (2000) appear to be better approximations.…”
mentioning
confidence: 75%
“…The uncertainty of p was computed from the combination of the error bars of the independent measurements of OGLE-LMC-CEP-0227 (P = 3.80 d, p = 1.21 ± 0.05, Pilecki et al 2013), δ Cep (P = 5.37 d, p = 1.288 ± 0.054, Mérand et al 2015), and the present measurement of RS Pup (P = 41.5 d, p = 1.250 ± 0.064). We did not average the error bars of the different p-factor measurements from the HST/FGS distances as the degree of correlation between them and the possible associated systematics are uncer- Pilecki et al (2013) and Gieren et al (2015), and we selected only the best p-factor of δ Cep derived by Mérand et al (2015). In agreement with the present results, Breitfelder et al (2016) also concluded from a fit to the complete sample of measured p-factors that a constant value of p = 1.324 ± 0.024 (1σ from our value) reproduces the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A full description of the code can be found in Mérand et al (2015) 2 . Briefly, this tool is based on the parallax-of-pulsation method (also called the Baade-Wesselink method), i.e.…”
Section: Algorithmmentioning
confidence: 99%